Substrate for holding hydrogel
The hydrogel retention substrate, composed of a wet nonwoven fabric with specific synthetic fibers, addresses the issue of uniform hydrogel retention and compression resistance, ensuring effective and stable hydrogel applications.
Patent Information
- Application Number
- JP2021016340
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-27
- Filing Date
- 2021-02-04
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-02-04
AI Technical Summary
Existing substrates fail to uniformly hold hydrogels when applied or impregnated, leading to variations in adhesiveness and poor retention of hydrogel solutions, especially under compression.
A hydrogel retention substrate made of a wet nonwoven fabric containing main synthetic fibers, such as polyester, and binder synthetic fibers, like core sheath type fibers, which provides high compression resistance and uniform fiber distribution for effective hydrogel retention.
The substrate achieves uniform holding and retention of hydrogels, even under compression, due to its high compression resistance and optimized fiber composition, enhancing the stability and usability of hydrogel applications.
Smart Images

Figure 0007666940000003 
Figure 0007666940000004 
Figure 0007666940000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a substrate for retaining a hydrogel. [Background technology]
[0002] Hydrogel is a general term for substances that contain water. Gels are "polymeric substances with a three-dimensional structure that are insoluble in any liquid, and their swollen bodies", and when the liquid is water (the prefix "hydro" meaning water), they are called hydrogels. Specifically, they are things like konjac, agar, and jelly. Water-soluble polysaccharides (water-soluble polymeric substances formed by binding sugars) and proteins such as gelatin are bridged (crosslinked) between different molecules to have a three-dimensional structure and are made insoluble in water (water insoluble). The solubility of polymeric substances in water can be explained by the interaction between the polymeric substance and water. When the polymeric substance itself has the property of attracting water, the polymeric substance is surrounded by water and becomes soluble in water. However, even if the polymeric substance is soluble in water, if the polymer chains are bridged to form a three-dimensional mesh structure, it cannot dissolve in water and becomes a swollen body containing a lot of water inside the mesh structure. This is a hydrogel (Non-Patent Document 1).
[0003] Hydrogels are essentially polymeric substances with high affinity for water that swell in an aqueous medium. Depending on the application, hydrogels have various properties such as water absorption, swelling, moisture retention, adhesion, and electrical conductivity, and by utilizing these properties, they are used in a wide range of fields such as civil engineering, agriculture, food, medicine, cosmetics, and electricity.
[0004] Generally, hydrogels with low crosslinking density have a very high swelling ratio in water. Such hydrogels cannot support their own weight and lose strength to the point where they cannot stand on their own. Therefore, hydrophobic monomers are copolymerized to reduce the swelling ratio of the polymeric substance and provide strength while maintaining biocompatibility (Patent Document 1).
[0005] For example, Patent Document 2 describes how even if a hydrogel has lost strength to the point that it cannot support its own weight and cannot stand on its own, when it is impregnated into a fiber substrate, it can not only retain its shape but also acquire lubricity not found in conventional hydrogel materials.
[0006] For example, in Patent Documents 3 and 4, in order to solve the problem of variation in adhesion to the skin in a hydrogel sheet containing a nonwoven fabric as an intermediate substrate, the degree of waviness is controlled within a specific range to suppress the variation in adhesion, since the variation in adhesion occurs due to the nonwoven fabric, which is the intermediate substrate, being slightly wavy inside the hydrogel sheet. However, no consideration has been given to a nonwoven fabric that can uniformly hold a hydrogel when the hydrogel is applied or impregnated. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Special Publication No. 2017-531737 [Patent Document 2] JP 2020-120825 A [Patent Document 3] JP 2020-97216 A [Patent Document 4] JP 2020-19842 A [Non-patent literature]
[0008] [Non-Patent Document 1] Regenerative Medicine, Vol. 11, No. 3, pp. 57-59, 2012 Summary of the Invention [Problem to be solved by the invention]
[0009] In view of the above problems, the present invention has an object to provide a substrate for holding a hydrogel that can hold a hydrogel uniformly when the hydrogel is applied or impregnated. [Means for solving the problem]
[0010] The means for solving the above problems are as follows. (1) A substrate for retaining hydrogel, which is made of a wet-laid nonwoven fabric containing at least a main synthetic fiber and a binder synthetic fiber. (2) The hydrogel-retaining substrate according to (1), wherein the main synthetic fiber is a polyester fiber and the binder synthetic fiber is a core-sheath fiber. (3) A hydrogel-retaining substrate according to (1) or (2), containing, as the main synthetic fiber, a fiber having a single fiber strength of 5.0 cN / dtex or more. (4) The substrate for retaining a hydrogel according to any one of (1) to (3), having the following compression resistance TM / TO of 0.7 or more. Compression resistance TM / TO: Three layers of hydrogel-holding substrate were stacked, and the compression deformation speed was set to 0.02 mm / sec, and the pressure was 50 gf / cm 2 Thickness TM (mm) at pressure 0.5gf / cm 2 This is the value divided by the thickness TO (mm) at time. Effect of the Invention
[0011] The hydrogel-retaining substrate of the present invention is capable of uniformly retaining a hydrogel when the hydrogel is applied or impregnated therein. [Brief description of the drawings]
[0012] [Figure 1] This is a photograph of the surface of a substrate for retaining hydrogel, which is made of a wet-laid nonwoven fabric produced on a wet papermaking machine using polyester fiber (main synthetic fiber) and core-sheath fiber (synthetic binder fiber). [Diagram 2] 1 is a photograph of the surface of a hydrogel-retaining substrate made of a polyester dry nonwoven fabric produced by a spunbond method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The hydrogel-retaining substrate of the present invention will be described in detail below.
[0014] In this specification, the "hydrogel-holding substrate" may be abbreviated to "substrate".
[0015] In the present invention, the substrate for retaining hydrogel is made of a wet-laid nonwoven fabric containing at least a main synthetic fiber and a binder synthetic fiber. The substrate made of a wet-laid nonwoven fabric is manufactured using a general paper manufacturing device. In general, the main synthetic fiber and the binder synthetic fiber cut to a fiber length of 20 mm or less are uniformly dispersed in water by a pulper dispersion device to prepare a fiber dispersion, and the fiber dispersion is poured onto a papermaking wire of a papermaking machine such as a cylinder papermaking machine, a Fourdrinier papermaking machine, or an inclined wire papermaking machine, and excess dispersion water is removed below the papermaking wire, and the fibers on the papermaking wire are drawn up and dried to produce a nonwoven fabric. The solid content concentration of the fibers in the fiber dispersion poured onto the papermaking wire is preferably 0.001 to 0.5%, and the fibers are uniformly dispersed on the papermaking wire to form a nonwoven fabric. Therefore, the substrate of the present invention made of a wet-laid nonwoven fabric has fibers uniformly spread as shown in FIG. 1, and has good formation, making it possible to uniformly retain the hydrogel. On the other hand, in the case of a substrate made of dry nonwoven fabric produced by the spunbond method, there is no process for uniformly dispersing the fibers, so there are areas with a high and low amount of fibers that make up the substrate, as shown in Figure 2, and the hydrogel cannot be held uniformly.
[0016] In the present invention, examples of polymeric substances that serve as raw materials for hydrogels include water-soluble polymers such as polyvinyl alcohol, polyacrylamide, polyacrylic acid, etc., crosslinked copolymers of water-soluble polymers such as polyvinyl alcohol, polyacrylamide, polyacrylic acid, etc., and natural polymers such as agarose, alginic acid, gelatin, etc. Hydrogels are useful materials because of the high water content of the polymeric substances, their high flexibility, and their high affinity with living bodies, and are widely used in the fields of medical materials, the environment, daily necessities, etc.
[0017] Hydrogels are weak and easily broken when used alone, so the drawbacks of hydrogels alone are eliminated by coating or impregnating a strong substrate with a solution of polymeric substances (hydrogel solution), which are the raw material for hydrogels. In general, the hydrogel solution is poured into a container to the desired depth and then irradiated with electron beams or ultraviolet rays to form the hydrogel. This causes the problem of poor productivity.
[0018] The present invention has discovered a substrate that allows a hydrogel solution to easily penetrate into the substrate when applied or impregnated, retains the hydrogel solution that has penetrated into the substrate, and is capable of retaining the hydrogel even when compressed in the applied or impregnated state.
[0019] In the substrate of the present invention, the main synthetic fiber is a fiber that does not melt by heat treatment (e.g., drying treatment, heat calendaring, etc.) during production with a wet paper machine, forms the skeleton of the substrate, and controls the strength and porosity for retaining the hydrogel solution. Examples of the main synthetic fiber include polyester-based, polyolefin-based, polyamide-based, polyacrylic-based, vinylon-based, vinylidene, polyvinyl chloride, benzoate, polychlar, and phenol-based fibers. In particular, polyester-based fibers are preferred because of their high resistance to electron beams and ultraviolet light irradiation. Fibers having irregular cross sections such as T-shaped, Y-shaped, and triangular cross sections can also be included.
[0020] The main synthetic fiber is a fiber that forms the skeleton of the substrate, and in order to control the porosity of the substrate, it is necessary to suppress deformation when the substrate is compressed. In order to suppress deformation, it is preferable to select a fiber with high single fiber strength. The single fiber strength is the load value when the fiber breaks using a tensile tester with a gripping distance of 20 mm according to JIS L 1015 (2010). When the main synthetic fiber contains a fiber with a single fiber strength of 5.0 cN / dtex or more, the effect of suppressing deformation when the substrate is compressed can be increased. The ratio of the main synthetic fiber with a single fiber strength of 5.0 cN / dtex or more to the entire main synthetic fiber is preferably 20 to 100 mass%, more preferably 50 to 100 mass%, and even more preferably 100 mass%. When it is less than 20 mass%, the effect of suppressing deformation during compression is small.
[0021] The fiber diameter of the main synthetic fiber is preferably 3 to 30 μm, more preferably 5 to 25 μm, and even more preferably 10 to 20 μm. If the fiber diameter of the main synthetic fiber exceeds 30 μm, the uniformity of the substrate may not be ensured. Also, if the fiber diameter of the main synthetic fiber is less than 3 μm, the hydrogel solution may not easily penetrate into the substrate when applied or impregnated into the substrate.
[0022] The fiber length of the main synthetic fiber is preferably 1 mm to 20 mm, more preferably 3 mm to 15 mm, and even more preferably 5 mm to 10 mm. If the fiber length exceeds 20 mm, poor formation may occur. On the other hand, if the fiber length is less than 1 mm, the strength of the substrate may decrease.
[0023] The binder synthetic fiber has a property of being thermally melted by a heating treatment (e.g., drying treatment, heat calendaring, etc.) when the substrate is manufactured by a wet paper machine, and is a fiber that bonds the intersections between the main synthetic fiber and the binder synthetic fiber and between the binder synthetic fibers to increase the strength of the substrate. Examples of the binder synthetic fiber include composite fibers such as core-shell type fibers, parallel type fibers, and radially split type fibers. Examples of the core-shell type fibers include a combination of polypropylene (core) and ethylene vinyl alcohol (sheath), a combination of polypropylene (core) and vinyl acetate alcohol (sheath), a combination of polypropylene (core) and polyethylene (sheath), and a combination of high melting point polyester (core) and low melting point polyester (sheath), and the like. From the viewpoint of increasing the strength of the substrate, it is particularly preferable to use a core-shell type polyester-based binder synthetic fiber consisting of a combination of high melting point polyester (core) and low melting point polyester (sheath). In addition, monofilaments (fully melted type) made only of low-melting resins such as polyethylene, and hot-water-soluble binder synthetic fibers such as hot-water-soluble polyvinyl alcohol-based fibers tend to form a film during the heating process, but can be used as long as their properties are not impaired.
[0024] In the substrate of the present invention, the blending ratio of the binder synthetic fiber is preferably 20 to 80 mass %, more preferably 30 to 70 mass %, and even more preferably 30 to 60 mass %, based on the total fibers constituting the substrate. If the blending ratio of the binder synthetic fiber exceeds 80 mass %, the voids in the substrate may decrease, and the penetration of the hydrogel solution into the substrate may become poor. If the blending ratio of the binder synthetic fiber is less than 20 mass %, the mechanical strength of the substrate may decrease, the substrate may become fuzzed, or the compression resistance of the substrate may decrease, making it impossible to retain the hydrogel solution.
[0025] The fiber diameter of the binder synthetic fiber is preferably 1 to 20 μm, more preferably 3 to 18 μm, and even more preferably 5 to 15 μm. If the fiber diameter of the binder synthetic fiber exceeds 20 μm, the uniformity of the base material may not be ensured. Also, if the fiber diameter of the binder synthetic fiber is less than 1 μm, stable production of the fiber becomes difficult.
[0026] The fiber length of the binder synthetic fiber is preferably 1 mm to 15 mm, more preferably 1 mm to 10 mm, and even more preferably 1 mm to 7 mm. If the fiber length exceeds 15 mm, poor formation may occur. On the other hand, if the fiber length is less than 1 mm, the voids in the substrate may decrease, and the penetration of the hydrogel solution into the substrate may become poor.
[0027] The substrate of the present invention can be produced by a papermaking machine for producing general paper or wetlaid nonwoven fabric, for example, a papermaking machine in which a papermaking wire such as a Fourdrinier, cylinder or inclined wire is installed alone, a papermaking machine capable of making two or more multi-layered paper having two or more heads on the same papermaking wire such as a Fourdrinier or inclined wire, a combination papermaking machine in which two or more types of the same or different papermaking wires are installed online, etc. The wet paper formed on the papermaking wire is dried with a dryer such as an air dryer, Yankee dryer, cylinder dryer, suction drum dryer or infrared dryer.
[0028] The basis weight of the substrate of the present invention is not particularly limited, but is preferably 10 to 150 g / m 2 is preferable, and 15 to 120 g / m 2 More preferably, 20 to 100 g / m 2 More preferably, 150 g / m 2 If the thickness exceeds 10 g / m, the penetration of the hydrogel solution into the substrate may deteriorate. 2 If it is less than this, the strength of the base material may be insufficient, or the amount of hydrogel solution retained may be reduced.
[0029] The thickness of the substrate of the present invention is not particularly limited, but is preferably 50 to 1000 μm, more preferably 100 to 800 μm, and even more preferably 150 to 600 μm. If it exceeds 1000 μm, the penetration of the hydrogel solution into the substrate may be deteriorated, and if it is less than 50 μm, the amount of the hydrogel solution retained may be reduced.
[0030] In the substrate of the present invention, the density of the substrate is 0.05 to 0.6 g / cm 3 and preferably 0.1 to 0.5 g / cm 3 More preferably, 0.15 to 0.4 g / cm 3 More preferably, the density is 0.05 g / cm 3 If the density is less than 0.6 g / cm, the compression resistance of the base material will decrease and the hydrogel solution may not be retained. 3 If the thickness exceeds this range, the penetration of the hydrogel solution into the base material may deteriorate.
[0031] In the present invention, the compression resistance of the substrate is defined as the resistance to compression when the compression characteristics are evaluated using a compression tester KES-FB3 (manufactured by Kato Tech Co., Ltd.), with a compression deformation rate of 0.02 mm / sec and a pressure of 0.5 gf / cm 2 Thickness TO (mm) at pressure 50gf / cm 2 The thickness TM (mm) at time t was measured and evaluated by dividing TM by TO (TM / TO). The closer the value is to 1, the higher the compression resistance.
[0032] In the present invention, the compression resistance of the substrate is preferably 0.7 or more, more preferably 0.8 or more, and even more preferably 0.85 or more. When the compression resistance of the substrate is 0.7 or more, the effect of improving the penetration of the hydrogel solution into the substrate and increasing the retention of the hydrogel solution in the substrate can be obtained. Substrates having a compression resistance of 0.7 or more can be, for example, those in which the blending ratio of binder synthetic fibers to the total fibers constituting the substrate is 20 mass% or more, polyester fibers are used as the main synthetic fibers, core-sheath synthetic fibers are used as the binder fibers, and the density of the substrate is 0.15 g / cm 3 The above can be obtained by drying the substrate with a Yankee dryer when producing the substrate by a wet papermaking method, pressing a roll against the substrate just before the substrate emerges from the Yankee dryer when producing the substrate by a wet papermaking method and drying the substrate with a Yankee dryer, drying the substrate with multiple cylinder dryers when producing the substrate by a wet papermaking method, etc.
[0033] The substrate of the present invention may be appropriately blended with additives such as crosslinking agents, water repellents, dispersants, retention aids, paper strength agents, dyes, etc., as necessary, within the range that does not impair the properties of the substrate. In addition, the substrate may contain a thermoplastic resin to impart mechanical strength and water resistance. Examples of the thermoplastic resin include acrylic, vinyl acetate, epoxy, synthetic rubber, urethane, polyester, vinyl chloride, vinylidene chloride, polyvinyl alcohol, starch, and phenolic resins, and these may be used alone or in combination of two or more. EXAMPLES
[0034] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the examples, all parts and percentages are by weight unless otherwise specified.
[0035] Main synthetic fiber 1: Fiber diameter 8μm, fiber length 3mm, single fiber strength 3.5cN / dtex, acrylic fiber
[0036] Main synthetic fiber 2: Fiber diameter 7.4 μm, fiber length 5 mm, single fiber strength 4.5 cN / dtex, stretched polyester fiber (stretched PET fiber)
[0037] Main synthetic fiber 3: Fiber diameter 10.5 μm, fiber length 5 mm, single fiber strength 4.5 cN / dtex, stretched PET fiber
[0038] Main synthetic fiber 4: Fiber diameter 17.5 μm, fiber length 5 mm, single fiber strength 4.5 cN / dtex, stretched PET fiber
[0039] Main synthetic fiber 5: fiber diameter 24.7 μm, fiber length 10 mm, single fiber strength 4.5 cN / dtex, stretched PET
[0040] Main synthetic fiber 6: Fiber diameter 10.5 μm, fiber length 5 mm, single fiber strength 5.1 cN / dtex, stretched PET fiber
[0041] Main synthetic fiber 7: Fiber diameter 17.5 μm, fiber length 10 mm, single fiber strength 5.6 cN / dtex, stretched polyester fiber
[0042] Binder synthetic fiber 1: A core-sheath type polyester-based binder synthetic fiber (PET core-sheath type fiber, Melty (registered trademark) manufactured by Unitika Ltd.) with a fiber diameter of 14.3 μm and a fiber length of 5 mm, in which the core is polyethylene terephthalate (melting point: 260°C), the dicarboxylic acid components are terephthalic acid and isophthalic acid, the diol components are ethylene glycol and diethylene glycol, and the sheath is a non-crystalline copolymer polyester having a softening temperature of 75°C.
[0043] Binder synthetic fiber 2: Fiber diameter 10 μm, fiber length 3 mm, polyvinyl alcohol fiber (PVA fiber)
[0044] (Examples 1 to 10) 2m 3 After adding water to the dispersion tank, the materials were mixed in the ratios (parts by mass) shown in Table 1, dispersed at a concentration of 0.2% for 5 minutes, and stirred with an agitator to prepare a uniform papermaking slurry (concentration 0.2%). This papermaking slurry was made into a paper using a wet papermaking method with a cylinder papermaking machine, and the binder synthetic fiber was bonded in a Yankee dryer at 130°C to develop nonwoven strength, resulting in a basis weight of 40 g / m2. 2 A substrate made of a wet-laid nonwoven fabric was prepared.
[0045] Comparative Example 1 Commercially available basis weight 40g / m 2 A spunbond dry nonwoven fabric of polyethylene terephthalate was used as the substrate of Comparative Example 1. The surface of the nonwoven fabric was photographed with an electron microscope at 2000 times magnification, and 30 fibers were randomly selected to measure the fiber diameter. The average fiber diameter was calculated to be 15.3 μm.
[0046] Comparative Example 2 Commercially available basis weight 40g / m 2The polypropylene meltblown dry nonwoven fabric was used as the substrate of Comparative Example 2. The surface of the nonwoven fabric was photographed with an electron microscope at 2000 times magnification, and 30 fibers were randomly selected to measure the fiber diameter. The average fiber diameter was calculated to be 4.3 μm.
[0047] <Evaluation> The substrates of Examples 1 to 10 and Comparative Examples 1 and 2 were evaluated as follows, and the measurement results of the physical properties of basis weight, thickness, and compression resistance TM / TO are shown in Table 1. In addition, the formation, permeability of the hydrogel solution into the substrate, and retention of the hydrogel solution during compression were evaluated, and the results are shown in Table 2.
[0048] [Table 1]
[0049] [Table 2]
[0050] [Basic weight] The basis weight was measured in accordance with JIS P8124:2011.
[0051] [Thickness and Density] The thickness and density of the substrate were measured in accordance with JIS P8118:2014.
[0052] [Compression resistance (TM / TO)] The compression characteristics were evaluated by stacking three substrates using a compression tester KES-FB3 (manufactured by Kato Tech Co., Ltd.). The compression deformation speed was 0.02 mm / sec. The pressure was 0.5 gf / cm. 2 Thickness TO (mm) at pressure 50gf / cm 2 The thickness TM (mm) at that time was recorded, and the value obtained by dividing TM by TO (compression resistance TM / TO) was calculated. The closer the TM / TO value is to 1, the higher the compression resistance is, and the better the substrate is.
[0053] [Ground Condition] A sheet of the substrate was placed on top of black paper to evaluate the uniformity of the formation.
[0054] Evaluation criteria ◯: There is no variation in fiber distribution and the fabric is at a good level. △: Some variation in fiber distribution is observed, but still usable. ×: There is a great deal of variation in the distribution of fibers, to a level that is unusable.
[0055] [Hydrogel solution permeability into substrate] In a 2-liter container containing 800 ml of ion-exchanged water, 200 g of polyvinyl alcohol powder (Kuraray Co., Ltd., model number: 28-98) with an average polymerization degree of 1700 and a saponification degree of 98.00 to 99.00% was added while stirring, the container was closed, and the container was placed in a hot water bath of 90°C or higher while stirring for 2 hours, and then cooled to room temperature to obtain a 20% PVA aqueous solution in which the PVA powder had completely dissolved. This PVA aqueous solution was used as a hydrogel solution to produce a hydrogel sheet by the following method.
[0056] The hydrogel solution was poured into a color pan containing a glass rod of a ONE STEP PROCESSOR (manufactured by Mitsubishi Paper Mills, Ltd.), and the substrate was passed under the glass rod in the color pan to immerse the substrate in the hydrogel solution. The substrate was then passed between two rotating rubber rolls fixed at both ends with spring rings to produce a hydrogel sheet, and the permeability of the hydrogel solution into the substrate was evaluated.
[0057] Evaluation criteria ○: The hydrogel solution is uniformly permeated into the base material, and is at a good level. △: A few areas were observed where the hydrogel solution had not permeated the substrate, but the substrate was still usable. ×: The hydrogel solution barely penetrated, to a level unusable.
[0058] [Hydrogel solution retention during compression] In a 2-liter container containing 800 ml of ion-exchanged water, 200 g of PVA powder (Kuraray Co., Ltd., model number: 28-98) with an average polymerization degree of 1700 and a saponification degree of 98.00 to 99.00% was added while stirring, the container was closed, and the container was placed in hot water at 90°C or higher while stirring for 2 hours, and then cooled to room temperature to obtain a 20% PVA aqueous solution in which the PVA powder had completely dissolved. This PVA aqueous solution was used as a hydrogel solution to produce a hydrogel sheet by the following method.
[0059] The hydrogel solution was poured into a color pan containing a glass rod of a ONE STEP PROCESSOR (manufactured by Mitsubishi Paper Mills Co., Ltd.), the substrate was passed under the glass rod of the color pan to immerse the substrate in the hydrogel solution, and then the substrate was passed between two rotating rubber rolls fixed at both ends with spring rings to produce a hydrogel sheet. The hydrogel sheet was quickly cut into 10 cm squares, and placed on a smooth PET film laid on a horizontal desk. A flat glass plate of 10 cm square was then placed on top of the hydrogel sheet, and a weight was then placed on top so that the total mass of the sheet and the glass plate was 1.2 kg. The state of the hydrogel solution leaking out from the edges was observed.
[0060] Evaluation criteria ⊚: The hydrogel solution did not leak out at all, which was at a very good level. ◯: The hydrogel solution leaked slightly from one direction, but at a good level. △: The hydrogel solution leaked out from one direction, but was still usable. ×: A large amount of hydrogel solution leaked from two, three or four directions, to a level unusable.
[0061] Comparing Example 1, in which the main synthetic fiber is acrylic fiber, with Example 4, in which the main synthetic fiber is PET fiber, the TM / TO value, which indicates compression resistance, is 0.69 for Example 1 and 0.80 for Example 4, which shows that Example 4, in which the main synthetic fiber is PET fiber, has higher compression resistance and better retention of the hydrogel solution during compression.
[0062] Comparing Example 2 and Example 3, the TM / TO value of Example 2, in which the blending rate of the binder synthetic fiber was 10%, was 0.63, and the retention of the hydrogel solution when compressed was evaluated as △, whereas the TM / TO value of Example 3, in which the blending rate of the binder synthetic fiber was 20%, was 0.71, and the retention of the hydrogel solution when compressed was evaluated as ◯, which was good. However, slight fluffing was observed in the substrate of Example 3.
[0063] Comparing Example 3 and Example 4, the TM / TO value of Example 4, in which the binder synthetic fiber content was 50%, was 0.80, and the retention of the hydrogel solution upon compression was evaluated as good with a rating of ○. Compared to Example 3, no fuzzing was observed in the base material of Example 4, which was good.
[0064] A comparison between Example 4 and Example 9 shows that the permeability of the hydrogel solution into the substrate is better in Example 4, which uses a core-sheath type fiber, than in Example 9, which uses a PVA fiber as the binder synthetic fiber.
[0065] Comparing Example 4 and Example 10, Example 4, in which the binder synthetic fiber content is 50%, had a thicker substrate and better permeability of the hydrogel solution into the substrate than Example 10, in which the binder synthetic fiber content is 80%.
[0066] Comparing Example 5 and Example 11, Example 11, in which the main synthetic fiber had a single fiber strength of 5.1 cN / dtex, had a higher TM / TO than Example 5, in which the main synthetic fiber had a single fiber strength of 4.5 cN / dtex, and the retention of the hydrogel solution during compression was rated as ◎, which was very good.
[0067] A comparison of Example 6 with Examples 12 to 14 shows that Examples 12 to 14, which contain main synthetic fibers with a single fiber strength of 5.6 cN / dtex, have a higher TM / TO and are rated as excellent in terms of hydrogel solution retention during compression, compared to Example 6, in which the main synthetic fibers have a single fiber strength of 4.5 cN / dtex. A comparison of Examples 12 to 14 shows that a higher ratio of main synthetic fibers with a single fiber strength of 5.0 cN / dtex or more to the total main synthetic fibers results in a higher TM / TO, closer to 1, and higher compression resistance.
[0068] The substrate made of spunbonded dry nonwoven fabric in Comparative Example 1 had good permeability of the hydrogel solution into the substrate and good retention of the hydrogel solution when compressed, but had poor formation and the hydrogel solution did not permeate to a uniform thickness. The substrate made of meltblown dry nonwoven fabric in Comparative Example 2 had good formation, but had poor permeability of the hydrogel solution into the substrate and good retention of the hydrogel solution when compressed, to a level that was unusable. [Industrial Applicability]
[0069] The substrate of the present invention can be suitably used as a substrate for retaining a hydrogel.
Claims
1. A hydrogel-retaining substrate comprising at least a main synthetic fiber and a binder synthetic fiber, and used for the purpose of penetrating and retaining a hydrogel, the substrate being made of "a wet nonwoven fabric obtained by uniformly dispersing the main synthetic fiber and the binder synthetic fiber in water and carrying out a wet method," The main synthetic fiber is a polyester-based, polyolefin-based, polyamide-based, polyacrylic-based, vinylon-based, vinylidene, polyvinyl chloride, benzoate, polychlor, or phenol-based fiber, the binder synthetic fiber is a composite fiber selected from the group consisting of a core-sheath type fiber, a parallel type fiber, and a radially split type fiber, or a monofiber made of polyethylene, or a hot water soluble binder synthetic fiber; A substrate for retaining a hydrogel, characterized in that the following compression resistance TM / TO is 0.7 or more. Compression resistance TM / TO: Three layers of hydrogel holding substrates were stacked, and the thickness TM (mm) at a pressure of 50 gf / cm 2 was divided by the thickness TO (mm) at a pressure of 0.5 gf / cm 2 when the compressive deformation rate was 0.02 mm / sec.
2. 2. The hydrogel retention substrate according to claim 1, wherein the main synthetic fiber is a polyester fiber.
3. 3. The substrate for holding a hydrogel according to claim 1, wherein the binder synthetic fiber is a core-sheath type fiber.
4. The hydrogel retention substrate according to claim 3, wherein the core-sheath fiber is a combination of polypropylene (core) and ethylene vinyl alcohol (sheath), a combination of polypropylene (core) and vinyl acetate alcohol (sheath), a combination of polypropylene (core) and polyethylene (sheath), or a combination of high melting point polyester (core) and low melting point polyester (sheath).
5. 4. The hydrogel retention substrate according to claim 3, wherein the core-sheath type fiber is a combination of a high melting point polyester (core) and a low melting point polyester (sheath).
Citation Information
Patent Citations
Stretchable cataplasm
JP1991161434A
Staple fiber nonwoven fabric
JP2009062644A
Gel sheet and sheet-like cosmetic using the same
JP2009108008A
Composite nonwoven fabric for plaster agent and method of manufacturing the same
JP2009269821A
Wet-laid nonwoven fabric and textiles
JP2013209777A